10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Excessive alcohol use is a leading cause of preventable morbidity and mortality in the United States, causing 117 000 deaths from chronic causes and 61 000 deaths from acute causes each year. Local health departments may find it challenging to assess the local impacts of excessive alcohol use, limiting their ability to mount an effective public health response to mitigate related harms. We leveraged the Centers for Disease Control and Prevention's Alcohol-Related Disease Impact (ARDI) application (app) to estimate the average annual number of alcohol-attributable deaths (AADs) and resulting years of potential life lost (YPLL) by age group, sex, and race and ethnicity in Franklin County, Ohio, from 2022 through 2024. The ARDI app allows users to create and upload custom prevalence and mortality datasets to estimate local alcohol-attributable fractions, AADs, and YPLL for 58 underlying causes of death related to excessive alcohol use. On average, there were 680 deaths and 17 597 YPLL per year in Franklin County from 2022 through 2024. The average annual mortality rate per 100 000 residents for AADs was 50.7, which was similar to the mortality rate for drug overdoses in Franklin County in 2023 (51.6). These findings provide important context for local public health professionals and policymakers and provide a foundation for further assessment and public health response. Our use of the ARDI app at the local level may also be of interest to other local health departments that wish to study the impact of excessive alcohol use in their jurisdictions.